Immunosuppressive MDSCs induced by TLR signaling during infection and role in resolution of inflammation - RAY, ANURADHA; Chakraborty, Krishnendu; Ray, Prabir (Frontiers in Cellular and Infection Microbiology, 2013)
Ligand-mediated activation of toll-like receptors (TLRs) not only induces inflammation but also immune suppression, which is an emerging area of investigation. Multiple negative feedback intracellular mechanisms have been described that are brought into play to prevent uncontrolled TLR activation. However, the identification of TLR-induced regulatory myeloid cells is a relatively recent development that has ramifications in pathogen-induced disease state as well as in cancer. Our efforts to understand how a high dose of lipopolysaccharide (LPS), a ligand of TLR4, suppresses allergic airway inflammation led to the identification of myeloid cells that are CD11b+Griint(Ly6Gint)F4/80+ and are phenotypically and morphologically similar to myeloid-derived suppressor cells (MDSCs) which are best studied in the context of cancer. MDSCs have been also detected during infection by various bacteria, parasites and viruses, which can engage different TLRs. These TLR-induced myeloid cells produce different types of mediators to influence immune response and inflammation that can be either beneficial or detrimental to the host. One beneficial function of TLR4/MyD88-triggered MDSCs in the lung is to efferocytose apoptotic neutrophils to help resolve inflammation elicited during bacterial pneumonia. A better understanding of the generation and function of these regulatory cells would be helpful to harness their potential or suppress their function for disease-specific immune regulation.